New Product Development Using Lean Startup Methodology (Case Study : The Atsomee) (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2022)
Fashion itself is one of the dominant sub-sectors in contributing to the economy in Indonesia. The Atsomee is a new player in the sustainable fashion industry selling clothing for women. With so many competitors in the same field, The Atsomee must continue to pursue and innovate. The need for new products is one of the crucial things in running a business in the fashion sector. In addition, the existence of product variants is very much needed for The Atsomee because it has spent several months without launching a new product. This study uses the Lean Startup method in developing its new product. The use of this method involves the customer/prospective customer in determining product development with the hope that the resulting product is in accordance with the needs and desires of the customer itself. This study uses interviews and questionnaires to determine product validation, market validation, and also business validation. The results obtained will then be used as the main data for the manufacture of new products for The Atsomee.